Spectrally-resolved ultraviolet absorption measurements of shock-heated NO from 2000 K to 6000 K for the development of a two-color rotational temperature diagnostic. (April 2022) - Krish, Ajay; Streicher, Jesse W.; Hanson, Ronald K.
Highlights: Developed a rotational temperature sensor for non-equilibrium flows containing nitric oxide. Acquired spectrally-resolved nitric oxide absorption cross-section measurements at high temperatures at two different wavelengths. Compared spectroscopic model predictions of the NO gamma-bands to high-temperature cross-section data. Provided empirical adjustments to line-positions modeled for the NO gamma-bands. Inferred translational and rotational temperature by applying the temperature diagnostic developed in this work. Abstract: In high-enthalpy air flows, nitric oxide (NO) formation and removal involves multiple, complex energy transfer processes that occur under nonequilibrium conditions, thus motivating the need for diagnostic methods to probe such flows in laboratory settings. In this work, a rotational temperature diagnostic for NO was developed using a spectroscopic model (Stanford NO model) of the γ -bands of NO to inform optimal wavelength candidates for absorption using two continuous-wave (CW), ultraviolet (UV) lasers. Absorption cross-sections of shock-heated NO were measured with two CW UV lasers over a range of temperatures and wavelengths, and results were compared to the Stanford NO model. All measurements were completed behind reflected shocks in 0.4% and 2% mixtures of NO in argon (Ar). Fixed-wavelength cross-section measurements from 2000 K to 6000 K between 1 atm to 0.085 atm were made at nominal wavelengths of 226.1026 nm and 224.8155 nm. Additionally, fixed-temperature measurements were made over the wavelength range 226.1013 nm to 226.1035 nm at 0.8 atm. The combination of experiments provided temperature and wavelength sweep cross-sections to compare against the Stanford NO model. The formulation for the collisional broadening parameter, 2 γ, was divided into two temperature regimes, transitioning at 2500 K. Additionally, line positions of the R 11 ( 26.5 ), R 12 ( 34.5 ), Q 21 ( 26.5 ), and Q 22 ( 34.5 ) transitions around 224.8155 nm and the Q 11 ( 12.5 ), R 12 ( 19.5 ), P 21 ( 12.5 ), and Q 22 ( 19.5 ) transitions around 226.1026 nm were adjusted to best fit the cross-section data. A vibrational equilibrium assumption was used to determine the translational and vibrational temperatures at the point of cross-section determination, while a coupled vibration-dissociation (CVDV) model characterized the extent of dissociation at the point of cross-section determination. Data from both temperature-sweep and wavelength-sweep measurements agree to within ± 10% of the Stanford NO model, with most cross-sections falling within ± 5% of model predictions. Oxygen (O2 ) cross-sections measurements were also taken behind reflected shocks in dilute 2% O2 in Ar mixtures at 2000 K and 6000 K to quantify the interfering O2 absorbance at the chosen diagnostic wavelengths.